Emotional engagement and perceived empathy in live vs. automated psychological interviews. - Thomas J Nyman; Anna-Karin Noromies; Francesco Pompedda; Pekka Santtila; Jan Antfolk (PLoS ONE)
In clinical in-person conditions, social presence, perceived empathy, and emotional engagement are related to positive outcomes. In online settings, it is unclear how these factors affect outcomes. Here, in 10-15-minute interviews, we investigated the influence of automation. Participants (N = 75) engaged in one of three possible interviews: live semi-scripted, live scripted, or video scripted. In the first two, participants communicated with a live interviewer and, in the third, with pre-recorded interviewer questions and answers. Emotion recognition software revealed that expressed joy differed between conditions (χ2(2) = 18.08, p < .001); both live conditions had higher scores (vs. video scripted). Self-rated perceived interviewer empathy also differed between conditions in the same way (F[2, 72] = 9.445, p < 0.001). We found a positive correlation between perceived empathy and expressed joy (r = .35; p < .01). In sum, automatized interviews differed in perceived empathy and expressed emotion compared with live interviews.